2017
DOI: 10.1016/j.ijnurstu.2017.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of fall prevention in residential care facilities: A systematic review of barriers and facilitators

Abstract: Objectives: To identify the barriers and facilitators for fall prevention implementation in residential care facilities. Design: Systematic review. Review registration number on PROSPERO: CRD42013004655. Data sources: Two independent reviewers systematically searched five databases (i.e. MEDLINE, EMBASE, CINAHL, PsycINFO, and Web of Science) and the reference lists of relevant articles. Review methods: This systematic review was conducted in line with the Center for Reviews and Dissemination Handbook and repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 39 publications
(213 reference statements)
3
45
0
Order By: Relevance
“…However, several "setting specific" factors seem to affect implementation as well. For example, in a systematic review on fall prevention in residential care facilities, poor information transfer among care providers, staff, and family, and across shifts and lack of care plan communication were barriers (Vlaeyen et al, 2017). Similar barriers emerged in our review, implying that these "setting specific" factors should be taken into account in care innovations.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…However, several "setting specific" factors seem to affect implementation as well. For example, in a systematic review on fall prevention in residential care facilities, poor information transfer among care providers, staff, and family, and across shifts and lack of care plan communication were barriers (Vlaeyen et al, 2017). Similar barriers emerged in our review, implying that these "setting specific" factors should be taken into account in care innovations.…”
Section: Discussionsupporting
confidence: 63%
“…Similar barriers emerged in our review, implying that these "setting specific" factors should be taken into account in care innovations. As is suggested by Vlaeyen et al (2017), we also underline that a focus on modifiable barriers and facilitators such as communication is needed in implementation projects in daily practice.…”
Section: Discussionmentioning
confidence: 93%
“…Preventative measures such as exercise, education and vitamin D supplements have been shown to have a non- or inconclusive effect in the residential care facility population (Avenell, Mak, & O’Connell, 2014; Bunn et al, 2014; Cameron et al, 2012). Although a review of complex multifactorial intervention programs has shown a reduction of recurrent fallers (Vlaeyen et al, 2015), there are considerable barriers for implementation outside the highly controlled circumstances of a study (Vlaeyen et al, 2017). As an alternative to active interventions, compliant flooring, defined as a flooring with some level of shock absorbency, has been suggested as a potential method for reducing the risk of fall-injuries among a frail elderly population (Lachance et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This calls for improved implementation of evidence-based guidelines, which meet several barriers in practice, such as insufficient management support, staff time and funding (Ferlie & Shortell, 2001;Gray, Joy, Plath, & Webb, 2012;Vlaeyen et al, 2017). Therefore, insight is needed in both the costs and the potential savings of falls prevention to estimate the economic value of this approach.…”
Section: )mentioning
confidence: 99%
“…This calls for improved implementation of evidence‐based guidelines, which meet several barriers in practice, such as insufficient management support, staff time and funding (Ferlie & Shortell, ; Gray, Joy, Plath, & Webb, ; Vlaeyen et al., ).…”
Section: Introductionmentioning
confidence: 99%